Climate effects on the growth of Pinus latteri and Pinus kesiya at the Intakin Silvicultural Research Station, Chiang Mai Province, Thailand - Matayawee Naumthong; Kritsadapan Palakit; Khwanchai Duangsathaporn; Patsi Prasomsin; Pichit Lumyai (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Naumthong M, Palakit K, Duangsathaporn K, Prasomsin P, Lumyai P. 2021. Climate effects on the growth of Pinus latteri and Pinus kesiya at the Intakin Silvicultural Research Station, Chiang Mai Province, Thailand. Biodiversitas 22: 2512-2519. Relationship between the growth of two pine species, Pinus latteri and Pinus kesiya, and past climatic factors are studied. Standard dendrochronological techniques were used on 40 core samples obtained from 20 trees from each species to cross-date tree-ring width and determine the growth patterns of each species. Over a period spanning from 1980-2019 (P. latteri) and 1984-2019 (P. kesiya), the calculated mean ring-width values were 0.596 and 0.430 cm per year, respectively. An analysis of the relationship between tree-ring width of P. latteri and climatic data indicated a positive correlation with the relative humidity in April. However, a negative correlation was observed with the temperature in April and August. The factors limiting the growth of P. latteri the most were the temperature in August (r2=0.228; P<0.01). The index constructed for P. kesiya indicated a positive correlation with extreme minimum relative humidity in December and extreme maximum temperature in March. The factors limiting the growth of P. kesiya with a significant correlation, were the relative humidity in April (r2=0.173) and temperature in May (r2=0.184). These results can be used to plan the management of forest plantations and to select suitable areas for the cultivation of pine trees in Thailand